2019
DOI: 10.1128/iai.00745-19
|View full text |Cite
|
Sign up to set email alerts
|

Direct Microscopic Observation of Human Neutrophil-Staphylococcus aureus Interaction In Vitro Suggests a Potential Mechanism for Initiation of Biofilm Infection on an Implanted Medical Device

Abstract: The ability of human neutrophils to clear newly attached Staphylococcus aureus bacteria from a serum-coated glass surface was examined in vitro using time-lapse confocal scanning laser microscopy. Quantitative image analysis was used to measure the temporal change in bacterial biomass, neutrophil motility, and fraction of the surface area policed by neutrophils. In control experiments in which the surface was inoculated with bacteria but no neutrophils were added, prolific bacterial growth was observed. Neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…Despite neutrophils appearing to respond to biofilm infection by increasing migration velocity and displacement, their movements were less directed toward the implant/infection than neutrophils in sterile tissues. These observation are consistent with a recent report that a delay in neutrophil recruitment to the implant surface may permit S. aureus time to grow and form biofilm (Ghimire et al, 2019 ). We anticipate that neutrophil deviation is a result of S. aureus biofilm products interfering with neutrophil cytokine/chemokine signaling and the production of multiple leukocyte inhibitors and toxins (Rooijakkers et al, 2006 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite neutrophils appearing to respond to biofilm infection by increasing migration velocity and displacement, their movements were less directed toward the implant/infection than neutrophils in sterile tissues. These observation are consistent with a recent report that a delay in neutrophil recruitment to the implant surface may permit S. aureus time to grow and form biofilm (Ghimire et al, 2019 ). We anticipate that neutrophil deviation is a result of S. aureus biofilm products interfering with neutrophil cytokine/chemokine signaling and the production of multiple leukocyte inhibitors and toxins (Rooijakkers et al, 2006 ).…”
Section: Discussionsupporting
confidence: 93%
“…Neutrophils are the first line of cellular immune defense against invading bacterial pathogens; their coordinated recruitment and activity are essential to preventing and eliminating infection. Compared to macrophages, neutrophils have shown a much higher propensity for biofilm invasion and phagocytosis in vitro (Gunther et al, 2009 ; Thurlow et al, 2011 ; Ghimire et al, 2019 ). We observed significant differences in the cell migration behaviors of neutrophils in response to infected versus sterile implants.…”
Section: Discussionmentioning
confidence: 99%
“…However, the antimicrobial susceptibility of all the tested bacteria drastically decreased when assayed in SF, which represents an important issue considering that infections are likely to start from one single cell ( Gerlini et al, 2014 ) and joint infections might arise from the contamination of sporadic cells. Furthermore, Ghimire et al recently showed that neutrophils are unable to efficiently phagocytize staphylococcal aggregates exceeding 10 μm in diameter and that they are supposed to be recruited rapidly and in sufficient numbers to scavenge all bacterial cells and prevent them to aggregate and grow to critical dimensions ( Ghimire et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supportive of this finding is the implant–inoculum interplay concept of implant infection developed by Ghimire et al 30 Their in vitro work demonstrated that both time before exposure to neutrophils and quantity of initial bacteria inoculation were critical determinants of successful Staphylococci implant infection. Novel hypotheses in neutrophil identification and phagocytosis of bacteria were explored, revealing that variation in the host–implant interface impacts the delicate balance between either bacteria persistence or eradication.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, new evidence produced by Ghimire et al 30 demonstrates the importance of bioburden, as a ratio of bacteria compared to the number of available neutrophils, in overwhelming the host immune system to establish a biofilm-associated infection. Summarized simply, at key early time points of exposure, a high ratio of neutrophils to bacteria seemed to clear the implant of colonization; whereas high bacteria to neutrophil ratio overwhelmed the system and allowed a biofilm to form.…”
Section: Introductionmentioning
confidence: 99%